Development of chemino card learning media (chemical domino cards) on elemental stability material - Suhardi Suhardi; Sumiati Side; Eda Lolo Allo (Pascasarjana Universitas Negeri Medan, 2024)
This reserach is research and development which aims to determine the level of validity, practicality and effectiviness of Chemino Card learning media as a learning media on elemental stability material which was carried out at X IPA. This development refers to the ADDIE development model which consists of five stages, namely: (1) analysis stage, (2) design state, (3) development stage, (4) implementation stage and (5) evaluation stage. The validity instrument is in the form of a validation sheet for media experts and material experts. Practical instrument include learning implementation observation sheets, teacher response questionnaires, student response questionnaires. The effectiviness instrument is a learning outcomes test. Research results show that: (1) the validity of the Chemino Card media based on material experts and media experts, respectively 3.33 and 3.46 which are included in the very valid category, (2) the practicatily of the Chemino Card media based on the observation of learning implementation, response questinnaire teachers and student respectively 96.67%, 90.03% and 83.42% which are included in the very high category, (3) effectiveness of Chemino Card media based on student learning outcomes that achieve class mastery of 92% that it is included in the effective category. Based in these data, it was concluded that Chemino Card learning media on elemental stanility material developed using the ADDIE model were stated to be valid, practical and effective for us in learning.